Improving Student Learning Outcomes in Indonesian Language Subjects Through the Implementation of the Problem Based Learning (PBL) Learning Model - Rahmayati, Rahmayati; Juniati, Juniati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The aim of this research is to improve the learning outcomes of class X-A students at SMA Negeri 4 Palu through the application of the Problem Based Learning (PBL) learning model in Indonesian language subjects. This research is class action research (Class Action Research) which consists of two cycles. Each cycle consists of action planning, action implementation, observation and reflection. The research subjects were class X-A students at SMA Negeri 4 Palu. Data sources come from teachers and students obtained through observation, interviews, tests and document review. The data analysis technique used is descriptive analysis. The research results show that: (1) The teacher's ability to carry out learning using the Problem Based Learning (PBL) method to improve student learning outcomes in Indonesian language learning in class X-A in cycle I has an average of 70% (quite good), while in the first cycle II to 87.5% (very good), this shows an increase of 10.5%. (2) There was an increase in student learning outcomes in learning Indonesian on biographical text material using the Problem Based Learning (PBL) method in class X-A SMA Negeri 4 Palu, where student learning outcomes in cycle I had an average of 73.14 with a completion percentage amounted to 42.86%, in cycle II it became 79.77 with a completion percentage of 88.57%. This shows an increase in student learning outcomes of 6.63.